2008
DOI: 10.1016/s1001-0742(08)62095-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-fouling ultrafiltration membrane prepared from polysulfone-graft-methyl acrylate copolymers by UV-induced grafting method

Abstract: Membrane fouling is one of the most important challenges faced in membrane ultrafiltration operations. The copolymers of polysulfone-graft-methyl acrylate were synthesized by homogeneous photo-initiated graft copolymerization. The variables affecting the degree of grafting, such as the time of UV (Ultraviolet-visible) irradiation and the concentrations of the methyl acrylate and photoinitiator, were investigated. The graft copolymer membranes were prepared by the phase inversion method. The chemical and morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 18 publications
(18 reference statements)
0
25
0
Order By: Relevance
“…This clearly demonstrates that the antimycobacterial activity is due to the silver nanoparticles embedded in the membrane and not due to the CA itself. The development of low fouling membranes or antifouling membranes is an intense area of research in membrane separation technology [27,28]. The use of nanoparticles in the manufacture of membranes allows for both a high degree of control over membrane fouling and the ability to produce desired structures [29][30][31].…”
Section: Antimycobacterial Membrane Studiesmentioning
confidence: 99%
“…This clearly demonstrates that the antimycobacterial activity is due to the silver nanoparticles embedded in the membrane and not due to the CA itself. The development of low fouling membranes or antifouling membranes is an intense area of research in membrane separation technology [27,28]. The use of nanoparticles in the manufacture of membranes allows for both a high degree of control over membrane fouling and the ability to produce desired structures [29][30][31].…”
Section: Antimycobacterial Membrane Studiesmentioning
confidence: 99%
“…Surface modification and blending techniques are mostly adapted due to their versatile controlling conditions. Surface modification methods include plasma [1][2][3], UV [4][5][6][7], electron beam surface induced grafting polymerization [8][9][10][11], and surface living/controlled radical polymerization [12][13][14][15][16][17][18]. Blending methods usually involve some amphiphilic copolymers, requiring to be synthesized elaborately through atom transfer radical polymerization (ATRP) [19][20][21] or reversible addition-fragmentation chain transfer polymerization (RAFT) [3,22].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, membrane fouling may possibly be controlled by changing the membrane surface chemistry. Previous investigations have demonstrated that, generally speaking, increasing membrane surface hydrophilicity can inhibit membrane fouling in water=wastewater treatment operations (7).…”
Section: Modification Of Nanofiltration Membranes 3347mentioning
confidence: 99%